2020
DOI: 10.1080/02656736.2020.1779356
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous microwave ablation of renal cell carcinoma: practice guidelines of the ultrasound committee of Chinese medical association, interventional oncology committee of Chinese research hospital association

Abstract: Imaging-guided percutaneous microwave ablation (MWA) with high thermal efficiency comprises rapid, successful management of small renal cell carcinomas (RCCs) in selected patients. Ultrasound Committee of Chinese Medical Association, Interventional Oncology Committee of Chinese Research Hospital Association developed evidence-based guidelines for MWA of RCCs after systematically reviewing the 1969-2019 literature. Systematic reviews, meta-analyses, randomized controlled trials, cohort, and case-control studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…Minimally invasive thermal therapy has been gradually applied to treat solid tumors as standard local therapy, including hepatocellular carcinoma, lung cancer, renal carcinoma, thyroid tumor, and so on [4][5][6][7][8] . However, recurrence may still occur after local ablation of tumors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Minimally invasive thermal therapy has been gradually applied to treat solid tumors as standard local therapy, including hepatocellular carcinoma, lung cancer, renal carcinoma, thyroid tumor, and so on [4][5][6][7][8] . However, recurrence may still occur after local ablation of tumors.…”
Section: Discussionmentioning
confidence: 99%
“…including hepatocellular carcinoma, lung cancer, renal carcinoma, thyroid tumor, and so on [4][5][6][7][8] . Several clinical trials have confirmed the local effect of ablation therapies with high complete ablation rates in the treatment of breast cancer [9][10][11] .…”
mentioning
confidence: 99%
“…MWA is increasingly used in the treatment of RCC and has achieved certain clinical results [ 7 , 8 ]. In a propensity-matched cohort study of 1955 patients with percutaneous MWA and laparoscopic PN for the treatment of cT1a RCC, it was found that there were no significant differences regarding oncologic outcomes and complications between the two therapies [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…This technique allows accurate positioning and planning of the ablation range, causes less trauma, takes less time to perform, has a wide application range, results in fewer postoperative complications, is repeatable, and can treat multiple lesions simultaneously [17,18]. MWA is now widely used in the treatment of a variety of solid tumors in various parts of the body [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%